ASEAN Unbound: Igniting the Digital Renaissance - Maspul, Kurniawan Arif; Ardhin, Muhammad (Journal of Regional Economics and Development, 2025)
ASEAN’s digital metamorphosis, driven by 400 million internet users and a $330 billion digital economy (Google et al., 2021), positions geospatial technology and open-source ERP systems as lifelines for survival and growth. These technologies tackle urbanization crises, disaster resilience, and SME empowerment—critical for a region where 68% will live in cities by 2030 (UNESCAP, 2020) and SMEs form 89% of businesses (ADB, 2022). Geospatial tools, like Indonesia’s One Map Policy resolving 80,000 land conflicts, and ERPNext slashing SME costs by 60% (Cavalcanti et al., 2022; OpenGov Asia, 2018), showcase ASEAN’s cost-innovation edge. Yet, fragmented data policies and skill gaps threaten progress. Government initiatives like Thailand 4.0 and Vietnam’s Digital Transformation Program signal a shift toward inclusive tech ecosystems, while firms like Grab export geospatial logistics globally. This study argues ASEAN’s blend of agility, affordability, and ethical innovation offers a blueprint for the Global South—proving technology can democratize power, save lives, and ignite a moral revolution in an era of crisis.